What's Really at Stake? Insights from Nova Scotia Teachers’ Use of Social Media during Collective Bargaining - Brickner, Rachel K. (Journal of Contemporary Issues in Education, 2024)
This study uses the case of the 2015-17 contract negotiations between the Government of Nova Scotia (Canada) and the Nova Scotia Teachers’ Union to understand (1) how the Government, the union, and individual educators framed the issues at stake in negotiations, and (2) how those perspectives were represented in traditional and social media. To answer these questions, I conducted two unique content analyses of news releases, social media posts, and traditional digital media over the course of negotiations. Results show that educators used social media to frame their work explicitly in terms of caring labour and to communicate with specificity and urgency the toll of their working conditions on their ability to meet the needs of their students and maintain their own well-being. However, active educators’ voices were rarely included in traditional media. These findings show that using social media does not guarantee that teachers’ perspectives will influence the broader public discourse. Moreover, they suggest that to the extent that care frames are employed in teachers’ strikes, it may be important for unions to develop an official campaign—in collaboration with rank-and-file educators—that is centred around care.